ISR8/IRF1-AS1 Is Relevant for IFNα and NF-κB Responses - Barriocanal, Marina; Prats-Mari, Laura; Razquin, Nerea; Prior, Celia; Unfried, Juan Pablo; Fortes, Puri (Frontiers in Immunology, 2022)
The study of the interferon (IFN) α-induced cell transcriptome has shown altered expression of several long non-coding RNAs (lncRNAs). ISR8 / IRF1-AS1 (IFN stimulated RNA 8), located close to IFN regulatory factor 1 (IRF1) coding gene, transcribes a lncRNA induced at early times after IFNα treatment or IRF1 or NF-κB activation. Depletion or overexpression of ISR8 RNA does not lead to detected deregulation of the IFN response. Surprisingly, disruption of ISR8 locus with CRISPR-Cas9 genome editing results in cells that fail to induce several key ISGs and pro-inflammatory cytokines after a trigger with IFNα or overexpression of IRF1 or the NF-κB subunit RELA. This suggests that the ISR8 locus may play a relevant role in IFNα and NF-κB pathways. Interestingly, IFNα, IRFs and NF-κB-responding luciferase reporters are normally induced in ISR8-disrupted cells when expressed from a plasmid but not when integrated into the genome. Therefore, IFNα and NF-κB pathways are functional to induce the expression of exogenous episomic transcripts but fail to activate transcription from genomic promoters. Transcription from these promoters is not restored with silencing inhibitors, by decreasing the levels of several negative regulators or by overexpression of inducers. Transcriptome analyses indicate that ISR8-disrupted cells have a drastic increase in the levels of negative regulators such as XIST and Zinc finger proteins. Our results agree with ISR8 loci being an enhancer region that is fundamental for proper antiviral and proinflammatory responses. These results are relevant because several SNPs located in the ISR8 region are associated with chronic inflammatory and autoimmune diseases including Crohn’s disease, inflammatory bowel disease, ulcerative colitis or asthma.